International student compliance: the regulatory dilemma of student and exchange visitor program (sevp)-certified urban community colleges - Odegbami, Omobonike B. (Kansas State University, 2022)
The purpose of this multi-case study was threefold: (a) to explore how Principal/Designated School Officials (P/DSOs) at Student and Exchange Visitor (SEVP)-certified urban community colleges make meaning of the international student regulatory environment; b) to provide a conceptual framework for understanding and explaining the practices and interventions for community college administrators to aid in improving immigration practices at community colleges; c) to propose practices and interventions for community college administrators and advisors to address the needs of international students served by the institution. This study explored how Principal/Designated School Officials (P/DSOs) interpret and make meaning of immigration regulatory environment. Historically, the United States has sought to maximize the talents and contributions of international students, export higher education, and take advantage of international students’ presence here as a foreign policy asset. Higher education institutions have emerged as critical partners in advancing national security while serving international student populations and maintaining a balance between governmental reporting responsibilities and institutional (and student-related) responsibilities. United States’ immigration laws and policies are constantly undergoing rapid and, in some instances, substantial changes that directly impact international students. These changing policies impact how P/DSOs, particularly in urban community colleges, enact and implement processes and procedures to keep international students in compliance. A Foucauldian knowledge-power theoretical framework was employed, situating federal regulations, institutional policy, and P/DSOs in a Panopticon of surveillance. Using qualitative methods, data was collected from in-depth interviews, and document analysis of federal documents pertaining to congressional committee meetings, regulatory documents, and legislative texts), NAFSA documents (opinion pieces, advocacy position statements and recommendations, research), newspaper and journal articles, and documents and materials from the community colleges being researched in the study relating to international student policies and procedures (including institutional websites). Themes that emerged include advocacy, fear, criminalization, prejudice, surveillance, and docile bodies. The findings document how immigration related regulations are interpreted and implemented.
Keywords: Principal designated school officials; International students; Immigration regulations